High-resolution mapping and terrain classification of Halimeda bioherms in the northern Great Barrier Reef - Zsanett Szilagyi; Luke Nothdurft; Stephanie Duce; Jody M. Webster; Mardi McNeil; Robin J. Beaman; Juan Carlos Braga; Trevor Graham; Maria Byrne; Amy Nau; Christopher Berry; Victorien Paumard; et al. (Geomorphology, 2026)

Experimental constraints on the role of temperature and pyrogenic mineral assemblage in wildfire-induced major and trace element mobilisation - Kristy Guerin; David Murphy; Stefan C. Löhr; Luke Nothdurft (Geochimica et Cosmochimica Acta, 2024)

In-situ mapping of monocrystalline regions on Mars - Brendan J. Orenstein; Michael W.M. Jones; David T. Flannery; Austin P. Wright; Scott Davidoff; Michael M. Tice; Luke Nothdurft; Abigail C. Allwood (Icarus, 2024)

Early Aboriginal pottery production and offshore island occupation on Jiigurru (Lizard Island group), Great Barrier Reef, Australia - Sean Ulm; Ian J. McNiven; Glenn R. Summerhayes; Pei-hua Wu; Magdalena M.E. Bunbury; Fiona Petchey; Quan Hua; Robert Skelly; Ariana B.J. Lambrides; Cassandra Rowe; Kelsey M. Lowe; Christian H. Reepmeyer; et al. (Quaternary Science Reviews, 2024)

Discovery of the dendrophylliid scleractinian Heteropsammia cochlea (Spengler, 1781) in Halimeda bioherms of the Northern Great Barrier Reef - Stefano Borghi; Matthew Clements; Monique Webb; Helen Bostock; Jody M. Webster; Mardi McNeil; Luke Nothdurft; Maria Byrne (Marine Biodiversity, 2023)
Halimeda bioherms on the Northern Great Barrier Reef (GBR) extend for over 6000 km 2 . To explore the ecological and biogeographical importance of these bioherms was one of the aims of a recent voyage on the Research Vessel (RV) Investigator . Through the use of underwater images and habitat sampling, we found populations of Heteropsammia cochlea (Spengler, 1781) living in the bioherms. The scleractinian coral genus Heteropsammia (Dendrophylliidae) is a group of solitary, apozooxanthellate, single-polyp corals with a widespread distribution in tropical and sub-tropical regions. Populations of H. cochlea were observed with individuals dispersed on open-sand habitat and among patches of Halimeda at 30–40 m water depth in mean densities of 89 and 29 corals per m 2 , respectively. Fluorescence microscopy was used to assess the presence of zooxanthellae, indicating that they are actively photosynthesising at these depths. These are the first observations of H. cochlea in association with the Halimeda bioherms on the Northern GBR.

Environmental controls on holocene reef development along the eastern brazilian margin - Belinda Dechnik; Alex C. Bastos; Laura S. Vieira; Jody M. Webster; Stewart Fallon; Yusuke Yokoyama; Juan-Carlos Braga; Manuel A. Pereira; Luke Nothdurft; Kelsey Sanborn; Rodrigo L. Moura; Gilberto Amado-filho (Coral Reefs, 2021)

Tracing nitrate sources using the isotopic composition of skeletal-bound organic matter from the calcareous green algae Halimeda - Dirk V. Erler; Luke Nothdurft; Mardi McNeil; Charly A. Moras (Coral Reefs, 2018)

Earliest diagenesis in scleractinian coral skeletons: implications for palaeoclimate-sensitive geochemical archives - Luke D. Nothdurft; Gregory E. Webb (Facies, 2009)

Microstructure of common reef-building coral genera Acropora, Pocillopora, Goniastrea and Porites: constraints on spatial resolution in geochemical sampling - Luke D. Nothdurft; Gregory E. Webb (Facies, 2007)